The Research Progress in the Application of Ceramic Nanofibers in Antibacterial Textile Materials - Miaoqing Xi; Xiaoming Yang (International Journal of Analytical Chemistry)
In order to investigate the application effect of ceramic nanofibers in antibacterial textile materials and improve the comprehensive use efficiency of antibacterial textile materials, ceramic nanofibers were introduced firstly and their fabrication methods and specific functions were discussed. Then, the antibacterial textile materials were introduced and their main uses and contributions were discussed. Finally, the application of ceramic nanofibers in antibacterial textile materials was investigated based on CiteSpace software. The results showed that the research on ceramic nanofibers had increased rapidly since 2000. Also, the number of the foreign literature retrieval was about 9,200 at most and 6,300 at least. The number of Chinese literature was about 6,000 at most and 1,000 at least. It can be seen that the current research of ceramic nanofibers is quite mature. But the quantity of the research on ceramic nanofibers in the application of antibacterial materials is relatively small. In the foreign literature retrieval, the number of the literature was about 1,300 at most and about 220 at least. In the Chinese literature retrieval, the number of the literature was about 600 at most and about 30 at least. It can be seen that the current domestic research on the application of ceramic nanofibers in antibacterial textile materials is not mature, but the foreign research is relatively good. The research not only provides a reference for the further research of ceramic nanofibers but also contributes to the improvement of antibacterial textile materials.